An Intersectional Application of Expectancy-Value Theory in an Undergraduate Chemistry Course - French, Allison M.; Else-Quest, Nicole M.; Asher, Michael; Thoman, Dustin B.; Smith, Jessi L.; Hyde, Janet S.; Harackiewicz, Judith M. (Sage, 2023)
The underrepresentation of women and Black, Latinx, and Native Americans within the United States scientific workforce is a persistent and multifaceted problem warranting an intersectional approach. Applying intersectionality to the expectancy-value theory of motivation, we examined initial motivation and subsequent achievement among a sample of undergraduate students (n = 687) enrolled in the STEM gateway course of introductory chemistry at a diverse four-year university. We found no racial/ethnic group differences in initial motivation, but small (d = .30) group differences in achievement. Results revealed a pattern of gender differences across both underrepresented (i.e., Black, Latinx, and Native American) and well-represented (i.e., White, Asian American) racial/ethnic groups such that, relative to men, women began the class with lower levels of confidence about their performance, but greater utility value and attainment value in learning chemistry. Consistent with expectancy-value theory, motivation at the beginning of the semester positively predicted final exam scores across gender and racial/ethnic intersectional groups. For Black, Latinx, and Native American students, attainment value was an especially strong predictor of subsequent achievement. Our findings point to the need to cultivate social contexts within undergraduate STEM education that promote all aspects of science motivation among students from underrepresented groups.